Multi-Domain System-Level Mathematical Modeling of Energy-Management System with High Accuracy - Wang, Mingyang; Tong, Xiaowen; Yue, Fan; Wu, Lindong; Huang, Xiaodong (International Conference on Integrated Circuit Design and Technology : proceedings, 2025)
For the first time, a multi-domain system-level model of energy-management system is presented for maximizing the battery service life. The simulation results agree well with the experimental results in various conditions, demonstrating high accuracy of this model. Moreover, this model is a white-box model and the battery micro behaviors under different conditions can be visualized. This work provides guidance to develop high-performance battery and highefficient energy-management strategy for extending the battery service life.